(3GdJhMjOs - (3CHh HcQ eMeO Hf ESMGb Hf NRjeIs ((3eMeO GdMQGfi s)
(3ChdgG (B:s
(3Chdg fGbU hChd GdehLhO efg CKfGA GdLRA GdQGHY (B: ( (3CHh HcQ GdYde Cf GdYHGS Hf YHO GdeWdH Yf GdfHi Udi Gddg Ydjg hSde ai HYO eG Hjf SeGA Edi GdJi JdjgG NdGa NHQ GHf eSYhO hdjS cPdc gh YfOfG s
(3BNQgG (B:s
(3Yf CHj gQjQI Cf GdfHi Udi Gddg Ydjg hSde bGd (B: ( (3Ef Cgd GdLfI djJQGAhf ai GdLfI HgPG bGd dfG eMeO Hf jMji dG CHYO Cf jchf YWGA Hf jSGQ bO SeYg ef CHj SYjO hGHi gQjQI QVi Gddg YfgeG BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3ai KeGfjI CLRGA MOjKs
(3GdcJGH QhGjI CHj eSde GdHNGQi Yf CHj YKeGf GdUGHhfi hYf CHj eMeO GdSeQbfOi Yf GdUGHhfi CjVkG s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds